Die Wirkung von Influencer Marketing auf das Kaufverhalten - Anne-Kristin Langner; Leonie Meyer; Nele Hansen (IU Internationale Hochschule, 2021)
– Pamela Reif, a German fitness influencer regulary reaches over eight million followers with her fitness posts and videos. Needless to say that many sports companies such as Puma reach out to her. What is so special about a relationship between an influencer and his/her followers and what actually influences consumers' purchase decision and purchase channel? Using logistic regressions, this study shows that the type of relationship and the believability of the influencer indeed influence the purchase decision. The perceived believability also influences the probability of purchasing a product presented by the influencer using the swipe-up function.
Keywords: 650; Influencer Marketing; Kaufentscheidungsprozess; Kaufverhalten; Social Media; Glaubwürdigkeit; Vertrauen